Potential of Methane (CH4), Nitrogen (N2), and Carbon Dioxide (CO2) from Eco-Enzyme with the Addition of Cow Feces Starter - Kamelia, Marlina; Ulmillah, Aulia; Pawhestri, Suci Wulan (Biology, Medicine, & Natural Product Chemistry, 2024)
Eco-enzyme solutions are generally used in the manufacture of disinfectants, floor cleaners, liquid fertilizers, preservatives and others. In this study, eco-enzyme was used as the main ingredient in the manufacture of biogas fermentation with the addition of cow feces as an additional starter in the fermentation. The aim of this study was to determine the content of CH4, CO2, N2, pH, temperature, and pressure in eco-enzyme fermentation with the addition of cow feces starter. Â his research is a quantitative research with the type of experimental research as well as direct observation data collection techniques and data analysis techniques using descriptive statistical analysis. The results showed that the treatment that produced the highest methane (CH4) gas was the P5 treatment with a concentration of 2.889%. 6,1. The highest volume pressure value was produced in the P5 treatment which was 70 ml. Nitrogen gas (N2) and carbon dioxide gas (CO2), the concentration of nitrogen gas (N2) from reactor P0 - P4 is in the range of 95.875-99.669 % and the concentration of carbon dioxide (CO2) from reactor P0 - P4 is in the range of 0.237 - 4.125 %.